EXPLORING TEACHERS’ PERCEPTIONS AND EXPERIENCES OF USING SOCIAL MEDIA FOR EDUCATIONAL PURPOSES - Mücahit, AYDOĞMUŞ; Edip, TUT; Yıldıray , KARADAĞ (Academic Journal of Psychology and Education (AJPE), 2023)
This qualitative study aimed to investigate teachers’ perceptions and experiences of using social media for educational purposes. Adopting a phenomenological approach, six teachers from primary and secondary schools were selected using criterion and snowball sampling methods. Data were analyzed using content analysis. The findings indicated that teachers use social media for both personal and professional development and consider it a valuable resource for educational content. Social media also helps overcome resource limitations and has a positive impact on student engagement. The study provides practical examples of how social media can be effectively used for educational purposes, making it useful for teachers, students, and other stakeholders in education. This research categorizes teachers’ experiences, highlighting their use of social media for educational purposes. Overall, the study sheds light on the educational value of social media and its potential for enhancing teaching and learning practices in the 21st century.